Pengembangan Media Video Pembelajaran Potensi Sumber Daya Alam pada Mata Pelajaran IPS di Kelas VIII SMP - Hanafi, Fachri; Novrianti, Novrianti; Anugrah, Septriyan; Ramayanti, Elsa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to develop valid and practical learning video media to be used as a supporting media in the learning process. The research was conducted using a type of research and development (R&D) with a 4D development model. The development procedures of this development are defined, design, development, and disseminate. The findings of this study, namely the development of learning video media using the Wondershare Filmora application in social studies subjects for grade VIII of junior high school, have been carried out in accordance with the development procedure that produces learning media in the form of documentary learning videos. This product has gone through the validation stage, based on the assessment of the results of material validation from teachers in the field of social studies at SMPN 8 Payakumbuh and media validation, namely Curriculum and Educational Technology lecturers. The validation results from material experts have been categorized as